The Pengaruh Kegiatan Ekstrakurikuler Rohani Islam terhadap Perkembangan Keterampilan Sosial (Social Skill) Siswa SMK Taruna Bhakti Cikarang Selatan - Muhammad Ridho Abdillah; Dedih Surana; Helmi Aziz (Bandung Conference Series: Islamic Education, 2024)
Abstract. The Rohis extracurricular activities are non-academic activities conducted outside of school hours, designed to develop students' talents and interests across cognitive, affective, and psychomotor aspects. Through these activities, students can enhance their social skills, such as communication, interaction, information management, and effective information delivery. This study aims to determine the impact of Rohis extracurricular activities on the development of social skills among students at SMK Taruna Bhakti Cikarang. The hypothesis proposed is that Rohis activities have a significant influence on students' social skills. Data collection was conducted using questionnaires to gather information about the Rohis activities and the students' social skills. The validation of the instruments was done using the Pearson Product Moment formula, while reliability was tested using the Spearman-Brown formula. The impact of Rohis activities on social skills was analyzed using the Pearson Product Moment after meeting the requirements of normality and linearity tests. The strength of the relationship between the two variables was measured using the coefficient of determination. The results showed a correlation of 0,505, indicating a moderate relationship between Rohis activities and students' social skills. Based on the coefficient of determination, Rohis activities contribute 25,5% to the development of social skills, while the remaining 74,5% is influenced by other factors, such as family, school, and community environments. Abstrak. Kegiatan ekstrakurikuler Rohis adalah aktivitas non-akademis yang diadakan di luar jam pelajaran untuk mengembangkan bakat dan minat siswa, mencakup aspek kognitif, afektif, dan psikomotorik. Melalui kegiatan ini, siswa dapat mengasah keterampilan sosial, seperti kemampuan berkomunikasi, berinteraksi, mengelola informasi, dan menyampaikannya dengan baik. Penelitian ini bertujuan untuk mengetahui pengaruh kegiatan ekstrakurikuler Rohis terhadap perkembangan keterampilan sosial siswa di SMK Taruna Bhakti Cikarang. Hipotesis yang diajukan adalah adanya pengaruh kegiatan Rohis terhadap keterampilan sosial siswa. Metode pengumpulan data menggunakan angket untuk memperoleh informasi mengenai kegiatan Rohis dan keterampilan sosial siswa. Validasi instrumen dilakukan dengan rumus Pearson Product Moment, dan reliabilitas diuji menggunakan rumus Spearman-Brown. Pengaruh kegiatan Rohis terhadap keterampilan sosial dianalisis dengan Pearson Product Moment, setelah memenuhi persyaratan uji normalitas dan linearitas. Besarnya hubungan antara dua variabel diukur dengan koefisien determinasi. Hasil perhitungan menunjukkan korelasi sebesar 0,505, yang mengindikasikan hubungan sedang antara kegiatan Rohis dan keterampilan sosial siswa. Berdasarkan koefisien determinasi, kegiatan Rohis berkontribusi sebesar 25,5% terhadap perkembangan keterampilan sosial, sedangkan 74,5% dipengaruhi oleh faktor lain, seperti lingkungan keluarga, sekolah, dan masyarakat.